Rediseño del gasoducto entre Popayán y Pasto con el uso de las herramientas Arcgis y Pipesim (2016)
The following dissertation project was made with the aim of redesign a gas pipeline from Popayan to Pasto guided by the company Erabal S.A.S., using Geographic information system (GIS), simulation tools such as ArcGIS and Pipesim. Starting by the geographic information system and data provided by the company Erabal S.A.S., an automatic routing tool was developed using the ArcGIS software, with which a selection of a starting and final spot can be established in order to draw a pipeline rout on the map considering basic design factors for instance, main roads, water bodies, rivers, cities or towns, geological faults and indigenous communities. Similarity it was developed a detailed study of class location, which is a design variable that affects the security in terms of disaster prevention, determining the schedules and pipe thickness considering the class.